June jam - Roy, Ron, 1940- (Roy, Ron, 1940- Calendar mysteries., 2011)
As a Father's Day gift to the twins' Dad, Bradley, Brian, and their cousins Lucy and Nate try to identify and stop whatever creature is biting fruits and vegetables in the garden.